PERANAN GURU SEKOLAH DALAM MENCEGAH TERJADINYA TAWURAN DIKALANGAN PELAJAR (Studi di SMA Perintis 1 Bandar Lampung) - Latifah, Mar Atul; Syani, Abdul (SOCIOLOGIE, 2013)
This study aims to identify and explain the role of schools in preventing teachers brawl among students. The method used in this research is descriptive qualitative. Informants are determined by purposive, and selection of informants were purposively selected is based on predetermined criteria and using some other person or persons as key intermediaries to be able to recognize and relate to informants. Data was collected by in-depth interviews, observation, documentation. Further data analysis is done with the data reduction, display or presentation of data, and drawing conclusions and verification. research sites in Perintis 1 High School Bandar Lampung. Informants in this study were 5 people, consisting of three teachers and two Perintis 1 high school Bandar Lampung students. Based on the results of this study indicate that the factors that led to see the brawl and the impact caused by the brawl, Perintis 1 High School teacher trying to prevent Perintis high school students did not perform actions that violate norms like brawl. the role of the teacher in an effort to prevent the brawl includes Primary Prevention, preventive, and Treatment. The role of the teacher is effective enough to prevent brawls, evidenced by Perintis 1high school students there is never involved brawl between students.Keywords: The role of school teachers, prevent student brawls